Monetary policy shocks and the health of banks - Alexander Jung; Harald Uhlig (European Central Bank (ECB), 2019)
Based on high frequency identification and other econometric tools, we find that monetary policy shocks had a significant impact on the health of euro area banks. Information effects, which made the private sector more pessimistic about future prospects of the economy and the profitability of the banking sector, were strongly present in the post-crisis period. We show that ECB communications at the press conference were crucial for the market response and that bank health benefitted from surprises, which steepened the yield curve. We find that the effects of monetary policy shocks on banks displayed some persistence. Other bank characteristics, in particular bank size, leverage and NPL ratios, amplified the impact of monetary policy shocks on banks. After the OMT announcement, we detect that the response of bank stocks to monetary policy shocks normalised. We discover that, in the post-crisis episode, Fed monetary policy shocks influenced euro area bank stock valuations.
Keywords: E40; E52; G14; G21; 330; high-frequency identification; panel of individual banks; local projections; information effects